Diagnosis and surgical treatments of hepatocellular carcinoma with tumor thrombosis in bile duct: Experience of 34 patients - Qin, Lun-Xiu (World J Gastroenterol, 2004)
AIM: Hepatocellular carcinoma (HCC) with bile duct tumor thrombosis (BDT) is a rare event. The prognosis of this type of patients is very dismal. The aim of this study was to share the experience in the diagnosis and treatment of HCC with BDT, to further improve the prognosis of these patients. METHODS: Thirty-four patients of HCC with BDT received surgical treatment in authors’institute from July 1987 to January 2003 were reviewed retrospectively. The experience in the diagnosis and treatment, and the outcome of this type of HCC patients were summarized. RESULTS: Thirty of the 34 patients (88.2%) were positive for alpha-fetoprotein (AFP) (> 20 μg/L), and 12 patients (35.3%) were found having obstructive jaundice before operation, 18 cases were suspected of “obstruction of bile duct” preoperatively. The primary tumors were frequently located at the left medial (13 cases) or right anterior lobe (14 cases). Thirty-one patients received liver resections and removal of BDT, while the other 3 patients received removal of BDT combined with hepatic artery ligation and cannulation (HAL + HAI), or only removal of BDT because their liver function reservation and general condition could not tolerate the primary tumor resection. The 1-year survival rate was 71.4% (20/28). The longest disease-free survival was over 15 years. The intrahepatic tumor recurrence within 1 year after operation was found in 14 patients (14/28, 50.0%). CONCLUSION: Surgical removal of primary tumors and BDT is safe and beneficial to the HCC patients with BDT. Early detection, diagnosis, and surgical treatment are the key points to prolong the survival time of patients.